Experimental Application of High-content Screening in Evaluating the Induction of Cell-cycle Arrest and Apoptosis on Human Liver Cancer Cell Line Hep-G2 - Nghi, Do Huu; Thi Ngoc Hao, Vo; Thi Hong Nhung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2020)
This study discusses the results of the experimental application of high-content screening (HCS) techniques in evaluating the induction of cell-cycle arrest and apoptosis on human liver cancer cell line, Hep-G2. Accordingly, the bisbenzimide-stained cells (Hoechst 33342; 350 to 500 nM) were analyzed by using an Olympus scanˆR HCS-system to determine the cell-cycle phases (G 1 , S, and G 2 /M) and apoptosis as well. As a result, the cell-cycle arrest could be indicated by an increase in G 2 /M population of Hep-G2 cells after 24h exposure to zerumbone (Zer4; 9 µg/mL) and a similar observation could be made for paclitaxel (Pac; 4 µg/mL) as a reference substance. Keywords Apoptosis, cell-cycle arrest, high-content screening, human liver cancer cell line Hep-G2. References [1] D. Hanahan, R.A. Weinberg, Hallmarks of cancer: the next generation, Cell 144 (2011) 646–674. [2] M. Malumbres, M. Barbacid, Cell cycle, CDKs and cancer: a changing paradigm, Nat. Rev. Cancer 9 (2009) 153–166. [3] S. Diermeier-Daucher, et al., Cell type specific applicability of 5-ethynyl-2'-deoxyuridine (EdU) for dynamic proliferation assessment in flow cytometry, Cytometry A 75 (2009) 535-546. [4] J. Essers, et al., Nuclear dynamics of PCNA in DNA replication and repair, Mol. Cell Biol 25 (2005) 9350- 9359. [5] V. Roukos, et al., Dynamic recruitment of licensing factor Cdt1 to sites of DNA damage. J. Cell Sci. 124 (2011) 422-434. [6] M. Hesse, et al., Direct visualization of cell division using high-resolution imaging of M-phase of the cell cycle, Nat. Commun 3 (2012) 1076. doi: 10.1038/ncomms2089. [7] P. Cappella, F. Gasparri, M. Pulici, J. Moll, A novel method based on click chemistry, which overcomes limitations of cell cycle analysis by classical determination of BrdU incorporation, allowing multiplex antibody staining, Cytometry A 73 (2008) 626–636. [8] S. Diermeier-Daucher, et al., Cell type specific applicability of 5-ethynyl-2’-deoxyundine (EdU) for dynamic proliferation assessment in flow cytometry, Cytometry A 75 (2009) 535–546. [9] T. Yokochi, D.M. Gilbert, Replication labeling with halogenated thymidine analogs, Curr. Protoc. Cell Biol, 35 (2007) 22.10.1–22.10.14. [10] T.J. McGarry, M.W. Kirschner, Geminin, an inhibitor of DNA replication, is degraded during mitosis, Cell 93 (1998) 1043–1053. [11] H. Nishitani, S. Taraviras, Z. Lygerou, T. Nishimoto, The human licensing factor for DNA replication Cdt1 accumulates in G1 and is destabilized after initiation of S-phase. J. Biol. Chem 276 (2001) 44905–44911. [12] J. Pines, T. Hunter, Human cyclin A is adenovirus E1A-associated protein p60 and behaves differently from cyclin B, Nature 346 (1990) 760–763. [13] A. Stathopoulou, et al., Cdt1 is differentially targeted for degradation by anticancer chemotherapeutic drugs. PLoS ONE 7, e34621 (2012). [14] M. Hesse, A. Raulf, G.A. Pilz, C. Haberlandt, A.M. Klein, R. Jabs, H. Zaehres, C.J. Fügemann, K. Zimmermann, J. Trebicka, A. Welz, A. Pfeifer, W. Röll, M.I. Kotlikoff, C. Steinhäuser, M. Götz, H.R. Schöler, B.K. Fleischmann, Direct visualization of cell division using high-resolution imaging of M-phase of the cell cycle, Nat. Commun 3 (2012): 1076. [15] D.A. Ridenour, M.C. McKinney, C.M. Bailey, P.M. Kulesa, CycleTrak: a novel system for the semiautomated analysis of cell cycle dynamics. Dev. Biol 365 (2012) 189–195. [16] A. Roukos, et al., Cell cycle staging of individual cells by fluorescence microscopy, Nat. Protoc 10 (2015) 334-348. [17] E. Harlow, D. Lane, Fixing attached cells in paraformaldehyde, CSH Protoc 3 (2006) doi: 10.1101/pdb.prot4294. [18] G. Mazzini, M. Danova, Fluorochromes for DNA staining and quantitation, Method. Mol. Biol 1560 (2017) 239-259. [19] A. Gottfried, E. Weinhold, Sequence-specific covalent labelling of DNA, Biochem. Soc. Trans 39 (2011) 623-628. [20] J. Bucevičius, G. Lukinavičius, R. Gerasimaitė, The use of Hoechst dyes for DNA staining and beyond, Chemosensor 6 (2018) 1-18. [21] V. Kumar, A.K. Abbas, J.C. Aster, Robbins and Cotran Pathologic Basis of Disease, Ninth ed., Elsevier/Saunders, Philadelphia (2015). [22] N.A. Jensen et al., Establishment of a high content assay for the identification and characterisation of bioactivities in crude bacterial extracts that interfere with the eukaryotic cell cycle, J. Biotechnol 140 (2009) 124-134. [23] H.S. Rahman, et al., Zerumbone induces G2/M cell cycle arrest and apoptosis via mitochondrial pathway in Jurkat cell line, Nat. Prod. Commun 9 (2014) 1237-1242. [24] S.I. Abdelwahab, et al., Zerumbone inhibits interleukin-6 and induces apoptosis and cell cycle arrest in ovarian and cervical cancer cells, Intern. Immunopharm 12 (2012) 594-602. [25] M. Xian, et al., Zerumbone, A bioactive sesquiterpene, induces G2/M cell cycle arrest and apoptosis in leukemia cells via a Fas- and mitochondria-mediated pathway, Cancer Sci 98 (2007) 118-126. [26] A. Sehrawat, et al., Zerumbone causes Bax-and Bak-mediated apoptosis in human breast cancer cells and inhibits orthotopic xenograft growth in vivo, Breast Cancer Res. Treat. 136 (2012) 429-441. [27] Y.Z. Zhou, et al., Zerumbone induces G1 cell cycle arrest and apoptosis in cervical carcinoma cells, Int. J. Clin. Exp. Med. 10 (2017) 6640-6647.